Extensively Drug Resistance Enteric Fever in Tertiary Care Hospital - Bushra Feroz, Arshad Khushdil, Imran Ahmad Memon, Sadaf Nawaz, Maryam Shahzadi, Waqas Akhtar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Salmonella enterica causes typhoid and paratyphoid fevers. Pakistan and other South Asian nations with little resources, including those with poor sanitation and hygiene, are particularly susceptible to enteric fever. Enteric fever is a disease which is extensively resistant to majority of antibiotics and these strains are rapidly spreading in Pakistan, raising concerns about the global failure of antibiotics. Study design: Descriptive cross-sectional study. Place and duration of study: Department of Pediatrics, CMH Quetta from 1st July 2022 to 31st December 2022. Methodology: A hospital based study in which history of fever for minimum of three days in the previous seven days, and blood test recommendation from a doctor were requirements for enrolment in the study. Individuals who had blood cultures that tested positive for enteric fever were enrolled. Results: Salmonella Typhi made up 52(94%) of the isolates and S. Para typhi made up 6%. 33(60%) of isolates were extensively drug-resistant (XDR), resistant to first-line antibiotics, fluoroquinolones, and third generation cephalosporin’s, and 8(15%) of isolates were extremely drug-resistant (MDR) to first-line antibiotics. Conclusion: In the current region of Pakistan, enteric fever is widespread. Over the course of the monitoring period, the incidence of typhoid fever has risen. With the advent of XDR typhoid, resistance to antimicrobial agents has also increased. Keywords: Enteric fever, Burden, Salmonella typhi, Typhoid fever